2002
DOI: 10.1523/jneurosci.22-23-10182.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Muscarinic Acetylcholine Receptors Enhances the Release of Endogenous Cannabinoids in the Hippocampus

Abstract: Endogenous cannabinoids (endocannabinoids) are endogenous compounds that resemble the active ingredient of marijuana and activate the cannabinoid receptor in the brain. They mediate retrograde signaling from principal cells to both inhibitory ["depolarization-induced suppression of inhibition" (DSI)] and excitatory ("depolarization-induced suppression of excitation") afferent fibers. Transient endocannabinoid release is triggered by voltage-dependent Ca(2+) influx and is upregulated by group I metabotropic glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
236
1
14

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(269 citation statements)
references
References 60 publications
15
236
1
14
Order By: Relevance
“…First, it is likely that inhibition of the GABAergic input to pyramidal cells by exogenous and endogenous cannabinoids was enhanced, because carbachol increased the contribution of CB 1 receptor-bearing GABAergic axons to the GABAergic input to pyramidal cells. Second, it is possible that carbachol, by acting on Ga q/11 protein-coupled M 1 and M 3 muscarinic receptors of postsynaptic pyramidal neurons potentiated DSI, as it was shown previously in the hippocampus and the striatum of rodents (Kim et al, 2002;Ohno-Shosaku et al, 2003;Narushima et al, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…First, it is likely that inhibition of the GABAergic input to pyramidal cells by exogenous and endogenous cannabinoids was enhanced, because carbachol increased the contribution of CB 1 receptor-bearing GABAergic axons to the GABAergic input to pyramidal cells. Second, it is possible that carbachol, by acting on Ga q/11 protein-coupled M 1 and M 3 muscarinic receptors of postsynaptic pyramidal neurons potentiated DSI, as it was shown previously in the hippocampus and the striatum of rodents (Kim et al, 2002;Ohno-Shosaku et al, 2003;Narushima et al, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…In agreement with this idea, DSI is strictly dependent on M.A. Diana & A. Marty DSI/DSE: two forms of CB1R-mediated plasticity 15 intracellular calcium increase, while the production of endocannabinoids via muscarinic and group 1 mGluR receptors is not Kim et al, 2002;Chevaleyre & Castillo, 2003). Two possibilities can be proposed at this stage.…”
Section: The G-protein Coupled Receptor Pathway Of Retrograde Inhibitionmentioning
confidence: 72%
“…Indeed, Varma et al (2001) (and later Ohno-Shosaku et al, 2002a) confirmed that group I mGluR activation also led to the production of endocannabinoids in hippocampal CA1 cells, and showed that this pathway, although not mediating DSI, had a powerful modulatory effect on the phenomenon. Further work extended these findings by showing that the activation of muscarinic receptors of the m1 and m3 subtypes had effects similar to those of group I mGluR activation (Martin & Alger, 1999;Kim et al, 2002;Ohno-Shosaku et al, 2003).…”
Section: The G-protein Coupled Receptor Pathway Of Retrograde Inhibitionmentioning
confidence: 73%
See 2 more Smart Citations